Comprehensive biomaterials - Ducheyne, Paul (Elsevier, 2011)
This work provides a new standard reference for students and researchers interested in any aspect of biomaterials science and engineering.
Keywords: biologické materiály; biomedicínské inženýrství; biological materials; biomedical engineering; elektronické knihy; electronic books